(untitled) (Journal of Hama University, 2024)
This study aims to determine the effectiveness of using equine chorionic hormone (eCG) and human chorionic hormone (hCG) in inducing estrus in female cats. The study included 16 sexually mature and reproductively healthy cats of different breeds’ whose ages ranged between (1-3) years’ from a number of breeders in the city of Hama’ and it has been (4-5) months since the last period of estrus. Indicators of estrus induction in cats include potential breeding opportunities or pregnancy outside the reproductive season. The animals in the experiment were randomly divided into two equal groups. The females of the first group(experimental group) were given eCG intramuscularly at a dose of (100) IU in the first day’ then (50) IU in the second and third days’ then hCG injections (500) IU in the seventh day. As for the females of the second group (control group) they were given a physiological solution (1’5) ml intramuscularly at the same times as the hormones mentioned in the first group. After that the experimental animals were monitored since the beginning of the injection of the used hormones to ensure that they had estrus’ and that depended on the clinical signs of estrus and the time of their occurrence. signs of estrus were observed on female cats. in the experiment group which were given hormones from the first dose’ while the females of the control group did not show any signs of estrus. The results showed that the percentage of estrus in the first experiment group was (100%) unlike the second group which did not have estrus at all’ with a clear significant difference between the experiment group and the control group (P=0.0000). The highest incidence of estrus, with significant difference, occurred 24 hours after the first injection’ at a rate of 50%’ and estrus occurred at a rate 25% after 72 hours. We conclude from the study that equine chorionic hormone and human chorionic hormone are effective hormones in inducing estrus outside the reproductive season in cats.